The WTO in Crisis: Closing the Gap between Conversation and Action or Shutting Down the Conversation?. Issue 3 (7th July 2022) - Low, Patrick
Abstract: The multilateral trading system faces numerous challenges that are more profound than at any time in its seven-decade history. It has become commonplace to ask whether the system is in terminal decline. More than a dozen issues facing the WTO are identified in the paper, eight of which are defined as systemic. That is because they permeate and debilitate multiple facets of the workings of the WTO, including the capacity to negotiate, enforce disciplines, monitor policies, and ensure transparency. In no prioritized order, systemic issues arise in the areas of dispute settlement, development, decision-making, transparency, relations between states and markets, subsidies, emerging issues including climate change and digitalization, and trade and health. Other outstanding issues may not be as pervasive in impact, but can nevertheless undermine WTO relevance and effectiveness. All WTO members stand to lose in the absence of predictable multilateral trade rules that pre-commit parties to certain policies and processes. But in today's world, full convergence of all trade rules is a pipe dream. The system needs to balance convergence with managed divergence. Does the non-discrimination principle need to be layered by prior agreement in ways that ensure mutual gains from exchange?